Quem é quem?: a elite política Passo-Fundense (1945-1988) - Lottermann, Luiz Alfredo Fernandes (2020)
Through prosopographic method, this thesis analyses the political elite of Passo Fundo city between 1945 and 1988. In order to profile the political elite, the age, gender, professions, ethnicity, place of birth and level of education of mayors, vice mayors and councilmen are measured. Especially the ones who took office in the city council at some moment in the legislatures. As sources, it was used the newspapers Diário da Manhã and O Nacional, and the publication Gallery of ex-councilmen from 1947 to 1988, as well as the documents that are available at Regional Historical Archive, at Passo Fundo City Council, the City Hall and data provided by the TRE-RS on the elections in Rio Grande do Sul. In addition to that, this research discusses the process of political openness during the crisis that is responsable for to the fall of the dictatorship of the Estado Novo, led by Getúlio Vargas, and the emergence of the multi-party system, national political parties, and its organization in Rio Grande do Sul and Passo Fundo, between 1945 and 1964. Besides, after the 1964 civil-military coup, this work seeks to analyze the reordering of the country's political structure during the dictatorship, the effects of Institutional Act No. II on the municipality and the emergence of the bipartisan system, which leads to the realignment of local political leaders around ARENA, support party of the dictatorial regime, and MDB, whose opposition was controlled. Similarly, this work discusses the transition process from 1979 and the restoration of democracy at the end of the military dictatorship that began in 1964. Also, this thesis observes the electoral results in national and regional level, particularly in five elections that took place during the democratic period and in five elections that took place during the military dictatorship, as well as the performance of the candidates and political forces in the power struggle, and the representatives national and regional levels.